Back Cover: Protein–Protein Communication Mediated by an Antibody‐Responsive DNA Nanodevice (Angew. Chem. Int. Ed. 12/2022). Issue 12 (9th February 2022) - Ranallo, Simona; Sorrentino, Daniela; Delibato, Elisabetta; Ercolani, Gianfranco; Plaxco, Kevin W.; Ricci, Francesco
Abstract : Information processing in living cells results from the communication between DNA, RNA, and proteins. Drawing inspiration from these molecular communication systems, Simona Ranallo, Francesco Ricci, and co‐workers describe in their Communication (e202115680) the rational design and optimization of an antibody‐responsive, synthetic DNA‐based device that enables communication between pairs of otherwise non‐interacting proteins.